Family firm succession and performance. Issue 2 (19th January 2017) - Baek, H. Young; Cho, David
ABSTRACT: We analyse more than half a million businesses from the Census Bureau's 2007 Survey of Business Owners with less survivorship and size biases. After controlling for firm- and owner-specific characteristics, we find family businesses generate fewer receipts and less employment and payroll. Family businesses involving a second-generation owner-manager show better performance. On the other hand, those managed by founder-owners show worse performance. These results of all firms, mostly small businesses, are contrary to the previous studies of large public firms. However, for a subsample of 2064 businesses large enough to be listed on a US stock exchange, the results become consistent with the previous large-firm studies.